Caracterización morfológica de las llamas (Lama glama) de la raza Ch’acu de Cusco, Perú - Machaca Machaca, Virgilio (2020)
The study was conducted in herds of llamas of peasant organizations in the district of Checacupe, Cusco Region, Peru, to determine the biometric measurements and live weight of the Ch’acu llamas based on sex and age. The measurements were grouped in cephalic, heights at withers and rump, cane perimeter and live weight, under a randomized complete design analysis with 2x5 factorial arrangement (α=0.5). Cephalic measurements showed significant differences in favour of the male (p<0.05), but the length of ears was similar; the heights were similar; body length, dorsal length and distance between shoulders favoured females (p<0.05); the measurements of the neck of the male llamas are different (p<0.05), except the length of the neck and its lower perimeter; females exhibit greater thoracic perimeter (p<0.05), but the thoracic perimeter and depth were similar; the thickness of the cane was similar; and live weight does not show differences, but exhibits high variability. Regarding age, the biometric measures are directly related to the growth and development of the llamas (p<0.05), reaching maximum values, according to the variable, in the categories of four teeth and full mouth. Based on this, it can be indicated that the Ch’acu llama presents aptitudes for meat and fibre, consistent with historical data. There is also sexual dimorphism and a relatively rapid growth rate.